Knowledge, attitude, practices of inhalational therapy among nursing staff posted at tertiary care teaching hospital - Sharma, Shubhakaran; Chhabra, Gaurav; Luhadia, S. K. (International Journal of Research in Medical Sciences, 2017)
Background: Inhalational therapy for patients with chronic respiratory disorder can greatly benefit. Nurses are one of the major components of health care system of hospital and have an important role in education and training of patients. This study was planned to assess knowledge, attitude, and practices of inhalational therapy among nurses. Methods: This questionnaire based cross sectional study was conducted after taking permission from the institutional ethics committee in all the nurses of a tertiary care teaching hospital. This questionnaire consists of few socio-demographic questions and other questions for assessing level of knowledge, attitudes, and practices related to inhalational therapy. Incompletely filled questionnaire were excluded out for data analysis. Data was interpreted in percentage. Results: Total 344 (87.31%) questionnaires were analysed. 334 (97.09%) have heard the term inhalational therapy and 310 (90.12%) responded that it is preferred in respiratory disease. 117 (34.01%) nurses could not mention single side effect of inhalational therapy. 178 (51.74%) nurses always assess/observe the patient and 211 (61.34%) always train the patients for correct inhalational technique. 165 (47.97%) nurses responded that knowledge of inhaler use came from attending meetings, courses or workshops organized by scientific bodies. 163 (47.38%) nurses considered ‘Disease to be treated’ the most important variable while prescribing an inhalational device. Conclusions: The knowledge of inhalational therapy was satisfactory while the demonstration of inhaler techniques to patients was moderate in this study. So regular training courses and workshop should be conducted for the nurses about inhalational therapy practical approach.